Nitromethane conjugate addition to 2-[(1E,3E)-4-arylbuta-1,3-dien-1-yl]-4Hchromen- 4-ones - Albuquerque, Hélio (2017)
Chromone are a group of oxygen-containing heterocycles, which are often associated to important biological activities.1 Chromone derivatives are also seen as interesting scaffolds to input further functionalizations,2 most of them through chemical transformations such as oxidation, condensation, Diels-Alder or conjugate addition. Conjugate addition of carbon nucleophiles to electron-deficient alkenes is one of the most important methods available for carbon–carbon bond-forming reactions. A wide range of carbon nucleophiles easily undergo conjugate addition with various substrates such as chalcones, cinnamylideneacetophenones or styrylchromones. Following previous work of our research group involving the 1,6-conjugate addition of nitromethane to (E)-2- styrylchromones,3 herein we report the first reactivity studies in the nitromethane conjugate addition to the extended unsaturated π-system of 2-[(1E,3E)-4-arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones 1 (Scheme 1). The DBU catalyzed nitromethane addition reaction afforded the corresponding β-(nitromethyl)chromones 2 (1,6-conjugate addition) as major products. (E)-5'-(Nitromethyl)-3'-styryl-[1,1'-biphenyl]-2-ol 3 and 3'-aryl-2'-nitro-5'-(nitromethyl)spiro [chromane- 2,1'-cyclohexan]-4-one 4 derivatives were also isolated as minor products, which result from the addition of two nitromethane molecules, through tandem processes.